Market orientation and gender wage gaps: an international study - Martina Zweimüller; Rudolf Winter-Ebmer; Doris Weichselbaumer (Institute for the Study of Labor (IZA), 2007)
Two very different approaches are used to explore the relation between market orientation and gender wage differentials in international data. More market orientation might be related to gender wage gaps via its effects on competition in product and labor markets and the general absence of regulation in the economy. The first approach employs meta-analysis data and takes advantage of the fact that many studies already exist which use national data sources to the best possible extent. The second approach uses comparable micro data from the International Social Survey Programme (ISSP), which allows calculating internationally consistent gender wage residuals in the first place. By comparing these two very different methods of data collection we get a robust result relating higher levels of market orientation as proxied by the Economic Freedom Index with lower gender wage gaps.
Keywords: 330; Wirtschaftsordnung; Marktwirtschaft; Wettbewerb; Deregulierung; Frauenarbeitslohn; Geschlechterdiskriminierung; Welt